The study of the charge collection of the normal-collector configuration - Tan, Chee Chin. (2013)
Charge collection is one of the crucial processes to collect the induced current when a semiconductor sample is subjected to some external excitations such as the electron or photon beams. The charge collection probability is the basis in the study of this induced current particularly in the field of photonic devices, photovoltaic cells as well as in the characterization of semiconductor materials and devices. In this paper, the analytical expressions for the charge collection probability of the finite-dimension normal-collector configuration, with and without surface recombination at the free surfaces are presented. An excellent agreement has been found between the charge collection probability profiles computed using the presently derived analytical expressions and those obtained using a device simulator. The results have been used to study the effects of the various physical parameters on the charge collection probability. These analytical expressions are expected to enhance our understanding of the charge collection process.